Optimal Indications of Radioimmunotherapy in Nuclear Medicine: A Mini-Review - Vahidfar, Nasim; Ahmadzadehfar, Hojjat; Farzanefar, Saeed; Abbasi, Mehrshad; Salehi, Yalda; Saboktakin, Fateme; Jahanbin, Mahsa; Kashi, Mohsen B.; Eppard, Elisabeth; Biersack, Hans Jürgen (Current Radiopharmaceuticals, 2024)
Immunotherapy has emerged as a very considerable and potent therapeutic method in which immune inhibitors have gained a lot of attention in the curative field of various cancers. Under certain circumstances, when radiotherapy is accompanied by immunotherapy, the efficacy of the therapeutic procedure increases. Irradiated tumor cells follow a pathway called immunogenic cell death, which targets tumor associated antigens. The application of radiolabeled antibodies under the concept of “radioimmunotherapy” (RIT) makes the synergistic targeted therapeutic effect possible. Since antibodies themselves are cytotoxic, they can kill the cells that not only bind but are within the path length of their radiation emissions. RIT can be categorized as a substantial progress in nuclear medicine. The main concept of RIT includes targeting specified tumor-expressing antibodies. The mentioned purpose is achievable by formulation of radiolabeled antibodies, which could be injected intravenously or directly into the tumor, as well as compartmentally into a body cavity such as the peritoneum, pleura, or intrathecal space. RIT has demonstrated very optimistic therapeutic outcomes in radioresistant solid tumors. Wide ranges of efforts are accomplished in order to improve clinical trial accomplishments. In this review, we intend to summarize the performed studies on RIT and their importance in medicine.
Keywords: therapy